1992
DOI: 10.1172/jci115865
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of insulin mRNA levels and insulin secretion in HIT cells by avoidance of chronic exposure to high glucose concentrations.

Abstract: Glucose toxicity of the pancreatic beta cell is considered to play a secondary role in the pathogenesis of type II diabetes mellitus. To gain insights into possible mechanisms of action of glucose toxicity, we designed studies to assess whether the loss of insulin secretion associated with serial passages of HIT-T15 cells might be caused by chronic exposure to high glucose levels since these cells are routinely cultured in media containing supramaximal stimulatory concentrations of glucose. We found that late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
146
1
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(160 citation statements)
references
References 49 publications
9
146
1
4
Order By: Relevance
“…In fact, we have extended our studies toward examination of the expression of C/EBP␤ in pancreatic ␤-cells in animal models of diabetes mellitus, with preliminary results implying an involvement of this factor in the pathophysiology of glucotoxic alterations during the development and progression of this disease. 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we have extended our studies toward examination of the expression of C/EBP␤ in pancreatic ␤-cells in animal models of diabetes mellitus, with preliminary results implying an involvement of this factor in the pathophysiology of glucotoxic alterations during the development and progression of this disease. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Studies using in vivo animal models and in vitro ␤-cell lines have demonstrated that a reduction of insulin gene transcription by glucose toxicity is associated with the loss of transactivator proteins such as IDX-1/IPF-1/STF-1 and RIPE3b1-binding protein (5)(6)(7)(8)(9)(10). Because insulin gene transcription is both positively and negatively regulated, we sought to identify repressors that might also mediate the effects of glucose toxicity on insulin gene transcription.…”
mentioning
confidence: 99%
“…The reversal of diabetes in NOD mice by CFA and repeated exposure to C57 splenocytes indicated that restoration of endogenous islet function is achievable without islet transplantation and despite the poor glycemic control attained by insulin injections. The beneficial influence of glycemic control on the growth, survival, and function of cultured islets, as well as of transplanted islets in nonautoimmune settings, has been demonstrated (35,36). To determine whether the restoration of endogenous β cell function could be achieved more consistently with better control of blood glucose, we replaced insulin injections with the intraperitoneal implantation of alginate-encapsulated C57 mouse islets.…”
Section: Figurementioning
confidence: 99%
“…Glucose toxicity in the pancreatic islet beta cell secondarily leads to further defects in beta cell function, including decreases in insulin reporter activity, gene expression, content, and secretion (3). Antioxidants have been shown to prevent these adverse changes in experimental models (4,5).…”
mentioning
confidence: 99%